Dilemmas and tensions in the transition from university classroom to pre-professional practice in psychology students - Ramírez Ramírez, Leticia (Pontificia Universidad Católica del Perú, 2016)
The purpose of this paper is inquired into the different dilemmas and tensionsexperienced by psychology students in their transition from university classroom to the pre-professional practice as a therapist in high school. The research is located in the qualitative paradigm, was carried out with 16 students studying the last year of the Psychology formation, through qualitative observation and depth interviews in the context of pre-professional practice. Six dilemmas and tensions experienced by learners in the transition from the classroom to the pre-practice were featured. We discuss about how identities are constantly re-negotiated and the resources that promote regulation with identity tensions in the pre-practice of novice psychologists.